Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\frac{x-3}{3}-1=\frac{x}{-4}\)
\(\Leftrightarrow\frac{x-3}{3}-\frac{3}{3}=\frac{x}{-4}\)
\(\Leftrightarrow\frac{x-6}{3}=\frac{x}{-4}\)
\(\Leftrightarrow-4\left(x-6\right)=3x\)
\(\Leftrightarrow-4x+24=3x\)
\(\Leftrightarrow24=3x+4x\)
\(\Leftrightarrow7x=24\)
\(\Leftrightarrow x=\frac{24}{7}\)
b) \(\frac{5}{8}-\left(x-\frac{1}{2}\right)=\frac{-3}{4}\)
\(\Leftrightarrow\frac{5}{8}-x+\frac{1}{2}=\frac{-3}{4}\)
\(\Leftrightarrow\frac{5}{8}+\frac{4}{8}-x=\frac{-3}{4}\)
\(\Leftrightarrow\frac{9}{8}-x=\frac{-3}{4}\)
\(\Leftrightarrow x=\frac{9}{8}+\frac{3}{4}\)
\(\Leftrightarrow x=\frac{15}{8}\)
Tìm x :
a) \(2.x.\frac{-3}{4}=-\frac{5}{12}\)
\(\Rightarrow2x=-\frac{5}{12}:-\frac{3}{4}\)
\(\Rightarrow2x=\frac{5}{9}\)
\(\Rightarrow x=\frac{5}{9}:2\)
\(\Rightarrow x=\frac{5}{18}\)
Vậy : \(x=\frac{5}{18}\)
b) \(\frac{2}{3}+\frac{1}{3}.x=7\)
\(\Rightarrow\frac{1}{3}.x=7-\frac{2}{3}\)
\(\Rightarrow\frac{1}{3}.x=\frac{19}{3}\)
\(\Rightarrow x=\frac{19}{3}:\frac{1}{3}\)
\(\Rightarrow x=19\)
Vậy : \(x=19\)
c) \(\left(4.x+\frac{1}{8}\right)=\frac{3}{10}\)
\(\Rightarrow4.x=\frac{3}{10}-\frac{1}{8}\)
\(\Rightarrow4.x=\frac{7}{40}\)
\(\Rightarrow x=\frac{7}{40}:4\)
\(\Rightarrow x=\frac{7}{160}\)
Vậy : \(x=\frac{7}{160}\)
d) \(\frac{1}{3}.x-5=1\frac{1}{2}\)
\(\Rightarrow\frac{1}{3}.x-5=\frac{3}{2}\)
\(\Rightarrow\frac{1}{3}.x=\frac{3}{2}+5\)
\(\Rightarrow\frac{1}{3}.x=\frac{13}{2}\)
\(\Rightarrow x=\frac{13}{2}:\frac{1}{3}\)
\(\Rightarrow x=\frac{39}{2}\)
Vậy : \(x=\frac{39}{2}\)
e) \(-\frac{2}{3}.x+\frac{1}{3}=-\frac{1}{2}\)
\(\Rightarrow-\frac{2}{3}.x=-\frac{1}{2}-\frac{1}{3}\)
\(\Rightarrow-\frac{2}{3}.x=-\frac{5}{6}\)
\(\Rightarrow x=-\frac{5}{6}:\left(-\frac{2}{3}\right)\)
\(\Rightarrow x=\frac{5}{4}\)
Vậy : \(x=\frac{5}{4}\)
a: \(=\left(-\dfrac{25}{140}+\dfrac{245}{140}+\dfrac{32}{140}\right)\cdot\dfrac{-69}{20}\)
\(=\dfrac{252}{140}\cdot\dfrac{-69}{20}\)
\(=\dfrac{9}{5}\cdot\dfrac{-69}{20}=\dfrac{-621}{100}\)
b: \(=\left(6-2-\dfrac{4}{5}\right)\cdot\dfrac{25}{8}-\dfrac{8}{5}\cdot4\)
\(=\dfrac{16}{5}\cdot\dfrac{25}{8}-\dfrac{32}{5}=\dfrac{18}{5}\)
c: \(=\left(\dfrac{2}{24}+\dfrac{18}{24}+\dfrac{14}{24}\right):\dfrac{-17}{8}\)
\(=\dfrac{34}{24}\cdot\dfrac{-8}{17}=\dfrac{-1}{3}\cdot2=-\dfrac{2}{3}\)
c) pt <=> \(x-\frac{21}{5}=\frac{23}{7}< =>x=\frac{23}{7}+\frac{21}{5}=\frac{262}{35}\)
vậy x = \(\frac{262}{35}\)
d) \(x-\frac{3}{4}=\frac{51}{8}< =>x=\frac{51}{8}+\frac{3}{4}=\frac{57}{8}\)
vậy x = \(\frac{57}{8}\)
e) pt <=> \(\frac{7}{8}:x=\frac{7}{2}< =>\frac{7}{8}.\frac{1}{x}=\frac{7}{2}< =>\frac{7}{8x}=\frac{7}{2}< =>56x=14< =>x=\frac{14}{56}=\frac{1}{4}\)
vậy x = \(\frac{1}{4}\)
a) pt <=> \(x+\frac{11}{4}=\frac{17}{3}< =>x=\frac{17}{3}-\frac{11}{4}=\frac{35}{12}\)
vậy x = \(\frac{35}{12}\)
b) pt <=> \(\frac{x.7}{2}=\frac{19}{4}< =>x=\frac{19.2}{4.7}=\frac{38}{28}=\frac{19}{14}\)
vậy x = \(\frac{19}{14}\)
\(E=\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^8}\\ 3E=1+\frac{1}{3}+\frac{1}{3^2}+...+\frac{1}{3^7}\\ 3E-E=\left(1+\frac{1}{3}+\frac{1}{3^2}+...+\frac{1}{3^7}\right)-\left(\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^8}\right)\\ 2E=1-\frac{1}{3^8}\\ E=\frac{1-\frac{1}{3^8}}{2}\)
thank you!